Purification and characterization of bacteriocin produced by lactic acid bacteria in agos-os - Tan, Julie Diamante 1957-; Galvez, Flor Crisanta F. (1998., 1998)
Different types of bacteria, yeasts and molds were isolated and characterized from agos-os, a fermented meat and sweet potato mixture. The bacteria belonged to species of Enterococcus, Corynebacterium, Acinetobacter, Escherichia, Klebsiella, and Lactococcus. Yeasts were identified as Candida and Torulopsis spp. while molds belonged to Aspergillus, Mortierella and Phanerochaete spp. Mold and anaerobic bacterial counts increased while yeasts and aerobic bacterial counts decreased during fermentation. Six bacterial isolates with the widest zones of inhibition were selected for bacteriocin production. These isolates were found to have exactly the same morphological, physiological and biochemical characteristics. The ribosomal RNA sequence was found to be 99.5% identical with Enterococcus faecalis VRE 1492. The identification was confirmed through DNA homology test by the EMBL Genbank, Canada. This bacterium produced the L-isomer lactic acid. The identified bacterium was used for the production of bacteriocin. The amount of bacteriocin was optimized by growing the bacterium at different growth media, initial pH and fermentation time. Maximum production of bacteriocin was achieved in MRS (De Man Rugosa and Sharpe) medium (with glucose) t pH 7.50 and 8.50 from 8 to 20 hours of incubation at 30°C. The bacteriocin was partially purified using 90% ammonium sulfate precipitation followed by gel filtration using TSK Toyopearl HW-50F. Two active fractions, designated as G1 and G2 were separated with the latter having higher activity than the former. SDS-Page revealed that G2 was composed of at least three types of compounds as shown by the three narrow bands in between the two broad bands. Further purification of G2 through Anion Exchange Chromatography using DEAE Toyopearl 650-M produced another two active fractions, the first one being eluted with buffer while the second fraction was eluted with NaCl gradient. The crude bacteriocin from ammonium sulfate precipitation was characterized based on its reaction to certain enzymes and different pH and temperatures. Trypsin, chymotrypsin and lipase were found to inactivate the bacteriocin as early as 4 hours of exposure at 30°C. To a lesser degree, alpha-amylase inactivated the bacteriocin after 24 hours of incubation. The presence of lysozyme seemed to enhance the inactivation of bacteriocin. The crude bacteriocin possessed a wide spectrum of activity. It inhibited the growth of gram-positive bacteria such as Lactobacillus sake 15521 and Listeria innocua. The gram-negative bacteria such as Escherichia coli DH 5-alpha (with plasmid, PUC), Salmonella typhii and Staphylococcus aureus were weakly inhibited. These microorganisms that were inhibited by the bacteriocin are pathogenic ones. Other microorganisms such as Lactobacillus curvatus D 31685, Lactobacillus confusius M 23036, Lactococcus lactis MG 1363, Leuconoctoc paramesenteroides S 67831, Pediococcus pentosaceus M 58834, Saccharomyces cerevisiae EC19 (mutant), Saccharomyces cerevisiae SS 553 (wild type) and Escherichia coli JM 109 (no plasmid) were not inhibited. Most of these microorganisms that were not inhibited by bacteriocin are useful in food fermentation processes.
Thesis (Ph.D. Food Science)--University of the Philippines, Diliman.
Vita.
Keywords: Bacteriocins; Fermentation; Lactic acid bacteria